Using Ergonomic Analysis and Evaluation of Workloads to Optimize Workstations that Require Physical Work - Angela ALBU (USV Annals of Economics and Public Administration, 2021)
Without any doubt, we are living in a very modern, sophisticated, and computerized world, in which a great part of the activities done in the past by workers, are now carried out by machines or intelligent devices, capable to communicate with the environment and to make decisions according to the information received from there. The ergonomics science adapted during the time, introducing in its area of study the effects of the human-computer interaction, the new forms of stress, and the new factors which are affecting the work at the workstations. However, there are still workplaces where physical work is prevalent and where it is necessary to analyze the work conditions to improve them and to avoid injuries during the work. This study is based on the research which has used ergonomic analysis, namely the LEST method for the optimization of the work of handler workers at a Romanian company with several working points in different regions of the country. The working points are equipped with different endowments depending on the period when they operate. The study reveals that the handlers are facing different problems at their workstations depending on the technical level of the equipment they use and the organization of the work. The same tasks lead to different perceptions and different levels of fatigue for the workers. The ergonomic analysis offers the possibility to identify the stress factors for each workstation and optimize them to provide optimum work conditions in which the worker can perform in the best way.